Validation of a High-Performance Liquid Chromatographic Method with Diod Array Detection for the Quantification of Citral and Formulation of Insect Repellent Cream from Lemongrass Oil - Nguyen, Thi Thanh Binh; Thanh Tung, Bui; Thi Mai, Nguyen; Thi Hue, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2020)
Lemongrass oil derived from some species of grasses in the family of Poaceae (particularly Cymbopogon citratus ) posses a highly effective insect repellent potential. In Vietnam, this product is widely commercially available but its quality is not strictly controlled. From a formulator's perspective, lemongrass essential oil is not suitable for direct application on the skin because high concentrations of citral, major chemical constituent of this oil, may cause local irritation. In addition, this compound is volatile, resulting in a short repellent effect. Contributing to solve these problems, a high-performance liquid chromatography with diode array detection was developed for the simultaneous quantification of neral and geranial, two geometric isomers of citral. This method was used to examine the quality of some lemongrass oil samples in order to choose material for the preparation of insect repellent cream. Experimental research demonstrated that the stability of the lemongrass oil cream containing 6% of citral was significantly improved when using β -cyclodextrin, a cyclic oligosaccharides capable of protecting substances by capturing them in conical structure. The obtained product showed insect repellent effect against banded sugar ant Camponotus consobrinus . This effect did not change after 6 months of storage in conventional conditions. Keywords Citral, high performance liquid chromatography, quantification, insect repellent cream, lemongrass oil. References [1] H.O. Lawal, G.O. Adewuyi, A.B. Fawehinmi, A.O. Adeogun, S.O. Etatuvie, Bioassay of herbal mosquito repellent formulated from the essential oil of plants, Journal of Natural Products. 5 (2012) 109-115. http://journalofnaturalproducts.com/Volume5/15_Res_paper-14.pdf. [2] New York State Integrated Pest Management Program, Lemongrass oil profile active ingredient eligible for minimum risk pesticide use. https://ecommons.cornell.edu/bitstream/handle/1813/56130/lemongrass-oil-MRP-NYSIPM.pdf, 2019 (accessed 5 November 2019). [3] Organisation for Economic Co-operation and Development, Citral CAS N°:5392-40-5. https://hpvchemicals.oecd.org/UI/handler.axd?id=0ea83202-3f4f-4355-be4f-27ff02e19cb9, 2001 (accessed 5 November 2019). [4] R. Arun, K.C.K. Ashok, V.V.N.S.S. Sravanthi, Cyclodextrins as drug carrier molecule: a review, Scientia Pharmaceutica 76 (2008) 567-598. http://dx.doi.org/10.3797/scipharm.0808-05. [5] O.I. Adeniran, E. Fabiyi, A cream formulation of an effective mosquito repellent: a topical product from lemongrass oil (Cymbopogon citratus) Stapf, Journal of Natural Product and Plant Resources, 2 (2012) 322-327. https://pdfs.semanticscholar.org/13bf/993de8f77462335ebc07365adb38e56e706f.pdf. [6] P. Borman, D. Elder, Q2(R1) Validation of analytical procedures: text and methodology, in: A. Teasdale, D. Elder, R.W. Nims (Eds), ICH quality guidelines: an implementation guide, John Wiley & Sons Inc., Hoboken, 2018, pp. 127-166. [7] S. Agrawal, N. Haldankar, A. Jadhav, Formulation of natural mosquito repellent, International Journal of Advance Research, Ideas and Innovations in Technology 4 (2018) 11-17. https://www.ijariit.com/manuscripts/v4i1/V4I1-1143.pdf. [8] Vietnamese pharmacopoeia commission, Vietnamese pharmacopoeia V part 2, Medical Publishing House Co., Ltd, Ha Noi, 2018 (in Vietnamese). [9] M.A.B. Edris, A.S.Y. Mamat, M.S. Aslam, M.S. Ahmad, Insect repellent properties of Melaleuca alternifolia, Recent Advances in Biology and Medicine 2 (2016) 57-61. http://dx.doi.org/10.18639/RABM.2016.02.293742. [10] R. Gaonkara, S. Yallappab, B.L. Dhananjayac, G. Hegde, Development and validation of reverse phase high performance liquidchromatography for citral analysis from essential oils, Journal of Chromatography B. 1036 (2016) 50–56. http://dx.doi.org/10.1016/j.jchromb.2016.10.001. [11] D. Miron, F. Battisti, C.S.T. Caten, P. Mayorga, E.E.S. Schapoval, Spectrophotometric simultaneous determination of citral isomers in cyclodextrin complexes with partial least squares supported approach, Current Pharmaceutical Analysis 8 (2012) 401-408. http://dx.doi.org/10.2174/157341212803341735. [12] L. Huber, Validation and qualification in analytical laboratories, Informa Healthcare USA Inc., New York, 2007. [13] N.D. Wilson, M.S. Ivanova, R.A. Watt, A.C. Moffat, The quantification of citral in lemongrass and lemon oils by near‐infrared spectroscopy, Journal of Pharmacy and Pharmacology 54 (2002) 1257-1263. http://dx.doi.org/10.1211/002235702320402107. [14] N. Dudai, O. Larkov, E. Lewinsohn, Simple colorimetric measurement of citral in lemon scented essential oils using Schiff’s reagent, Future for Medicinal and Aromatic Plants, 26 (2004) 499-504. http://dx.doi.org/10.17660/ActaHortic.2004.629.64.